Case report: Foreign body aspiration requiring extracorporeal membrane oxygenation - Ginter, Dylan; Johnson, K. Taneille; Venettacci, Oliver; Vanderlaan, Rachel D.; Gilfoyle, Elaine; Mtaweh, Haifa (Frontiers in Pediatrics, 2023)
Introduction Foreign body aspiration is a common cause of respiratory distress in pediatrics, but the diagnosis can be challenging given aspirated objects are mostly radiolucent on chest radiographs and there is often no witnessed choking event. We present a case of a patient who was initially managed as severe status asthmaticus, requiring veno-arterial extracorporeal membrane oxygenation (VA-ECMO) for refractory hypercarbia and hypoxemia, but was later found to have bilateral bronchial foreign body aspiration. This case is unique in its severity of illness, diagnostic dilemma with findings suggesting a more common diagnosis of asthma, and use of ECMO as a bridge to diagnosis and recovery. Patient Case A previously healthy 2-year-old boy presented during peak viral season with a 3-day history of fever, cough, coryza, and increased work of breathing over the prior 24 hours. There was no reported history of choking or aspiration. He was diagnosed with asthma and treated with bronchodilator therapy. Physical examination revealed pulsus paradoxus, severe work of breathing with bilateral wheeze, and at times a silent chest. Chest radiographs showed bilateral lung hyperinflation. Following a brief period of stability on maximum bronchodilator therapies and bilevel positive pressure support, the patient had a rapid deterioration requiring endotracheal intubation, with subsequent cannulation to VA-ECMO. A diagnostic flexible bronchoscopy was performed and demonstrated bilateral foreign bodies, peanuts, in the right bronchus intermedius and the left mainstem bronchus. Removal of the foreign bodies was done by rigid bronchoscopy facilitating rapid wean from VA-ECMO and decannulation within 24 hours of foreign body removal. Conclusion Foreign body aspiration should be suspected in all patients presenting with atypical history and physical examination findings, or in patients with suspected common diagnoses who do not progress as expected or deteriorate after a period of stability. Extracorporeal life support can be used as a bridge to diagnosis and recovery in patients with hemodynamic or respiratory instability.